Implementasi Budaya Sekolah terhadap Penguatan Profil Pelajar Pancasila pada Siswa Kelas IV SDN 58 Lubuklinggau - Valen, Andri; Maharani, Tidi; Widaswari, Dea (JOEAI (Journal of Education and Instruction), 2024)
The purpose of this study is to describe the Implementation of School Culture towards Strengthening the Profile of Pancasila in Grade IV Students of SD Negeri 58 Lubuklinggau. Through the application of school culture to strengthen the profile of Pancasila students, grade IV students of SD N 58 Lubuklinggau are expected to be able to instill positive values contained in the six main elements of the Pancasila student profile. This research uses a descriptive method with a qualitative research approach because the research describes or describes facts or circumstances regarding factors that affect the strengthening of the profile of Pancasila students at SD Negeri 58 Lubuklinggau. This type of research is descriptive qualitative. The results of research on the implementation of school culture towards strengthening the profile of Pancasila have six kinds of categorization. In the first aspect of the Pancasila, the student profile obtained good categorization with a percentage of 61.05%, in the second aspect obtained sufficient categorization with a percentage of 60.03%, in the third aspect obtained sufficient categorization with a percentage of 60.19%, for the fourth aspect of the Pancasila student profile obtained good categorization with a percentage of 66.29%, in the fifth aspect obtained sufficient categorization to have a percentage of 57.06%, and the sixth aspect obtained sufficient categorization to have a percentage The lowest of the six aspects of the Pancasila profile is with a percentage of 52.25%. From the results of research data analysis, it can be seen that the percentage of scores in various aspects of the Pancasila profile there are several aspects that have a good and sufficient percentage of scores, but the percentage of scores obtained is still in the good category.